Anatomically preserved fossil cornalean fruits from the Upper Cretaceous of Hokkaido: Eydeia hokkaidoensis gen. et sp. nov. Issue 9 (9th September 2016) - Stockey, Ruth A.; Nishida, Harufumi; Atkinson, Brian A.
Abstract : PREMISE OF THE STUDY: The basal asterid clade Cornales radiated during the Late Cretaceous. However, our understanding of early evolutionary patterns and relationships remain obscure. New data from five permineralized fruits in calcareous concretions from the Upper Cretaceous (Coniacian‐Santonian) Haborogawa Formation, Hokkaido, Japan provide anatomical details that aid our knowledge of the group. METHODS: Specimens were studied from cellulose acetate peels, and three‐dimensional reconstructions were rendered using AVIZO. KEY RESULTS: Fruits are drupaceous, roughly pyriform, 2.9–4.3 mm in diameter, with a fleshy mesocarp, transition sclereids, and a stony endocarp of four to five locules, with the septa forming a cross or star‐like pattern in transverse section, distinct germination valves, and one apically attached anatropous seed per locule. Vascular tissue occurs in zones between the mesocarp and exocarp, in two rows within the septa, and prominent seed bundles can be traced throughout the fruit sections. Seeds have a single integumentary layer of radially flattened square to rectangular cells and copious cellular endosperm. A fully formed, straight, cellular dicotyledonous embryo, with closely appressed, spathulate cotyledons, is present within each seed. CONCLUSIONS: The unique combination of characters shown by these fruits is found in Cornaceae, Curtisiaceae, and Davidiaceae and allows us to describe a new taxon of Cornales, Eydeia hokkaidoensis gen. et sp. nov., with many similarities to extant Davidia involucrata . These fossils underscore the phylogenetic diversification of Cornales that was underway during the Late Cretaceous and support the hypothesis that a Davidia ‐like fruit morphology is plesiomorphic within Cornales.